Complexes of Nitric Oxide with Nucleophiles as Agents for the Controlled Biological Release of Nitric Oxide: Antiplatelet Effect - Diodati, Jean G; Quyyumi, Arshed A; Hussain, Nabeen; Keefer, Larry K (Thrombosis and Haemostasis, 1993)
Nitric oxide (NO) inhibits platelet aggregation. Accordingly, we hypothesized that complexes of diethylamine and spermine with NO (DEA/NO and SPER/NO, respectively), two vasodilators previously shown to release NO spontaneously in aqueous solution, may also be useful antiplatelet agents. Platelet aggregation was measured in whole blood or platelet-rich plasma by impedance aggregometry after addition of collagen. In whole blood, the dose response curve for DEA/NO added 1 min before collagen was similar to that for aspirin (60% inhibition at 10-4 M), while SPER/NO and sodium nitroprusside were less potent by an order of magnitude. In platelet-rich plasma, 10-6 M DEA/NO caused 60% inhibition, while SPER/NO and sodium nitroprusside were as active only at 10-5 M; aspirin’s potency was unchanged from that in whole blood. In vivo, DEA/NO and sodium nitroprusside produced significant platelet inhibition 1 min after intravenous injection in the rabbit at 50 nmol/kg. Similar in vivo platelet inhibition was observed with SPER/NO and aspirin, but only at higher dose. The effects of DEA/NO and sodium nitroprusside were transient, lasting less than 30 min after treatment, while the activity of SPER/NO and aspirin was sustained throughout the 30 min experiment. The magnitude and duration of the antiplatelet effects of DEA/NO and SPER/NO correlate with the rates at which they release nitric oxide spontaneously in aqueous solution. Thus, NO/nucleophile complexes merit further exploration both as research tools and as potential antiplatelet agents.